Mengembangkan Kemampuan Mengenal Bilangan 1-10 Melalui Media Kantong Pintar Di PAUD TGK Dikuta Banda Aceh - Cut Raziah; Khoiriyah Khoiriyah; Nasir Usman; Dina Amalia; Dewi Yunisari (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
The ability to recognize numbers among Group A children at PAUD Tgk Dikuta Banda Aceh is still relatively low, as reflected in the children’s limited ability to properly recognize numbers 1–10. One method to improve children’s number recognition skills is through playing the “smart pocket” game. This study aims to determine the development of children’s ability to recognize numbers 1–10 through the use of smart pocket media at PAUD Tgk Dikuta Banda Aceh. This research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of two actions. Every cycle included four stages: planning, implementation, observation, and reflection, with 12 children serving as the research subjects. Data collection techniques were carried out through observation and performance assessment. The results of the study indicate that the application of smart pocket media can improve children’s ability to recognize number symbols 1–10. In Cycle I, the children’s abilities began to improve toward the “Developing as Expected” (BSH) category, although the progress was still gradual, with a success rate of 17% in Action I and 83% in Action II. A similar improvement was observed in Cycle II, marked by an increasing number of children consistently reaching the “Developing as Expected” (BSH) and “Very Well Developed” (BSB) categories, with a success rate of 58% in Action I and 83% in Action II. Overall, the percentage of success increased from 0% in the pre-cycle to 83% in both Cycle I and Cycle II, indicating that the smart pocket media is effective in facilitating children’s basic numeracy understanding in a concrete, enjoyable, and structured manner